2020
DOI: 10.1111/jcmm.15189
|View full text |Cite
|
Sign up to set email alerts
|

SOX9‐activated PXN‐AS1 promotes the tumorigenesis of glioblastoma by EZH2‐mediated methylation of DKK1

Abstract: Increasing evidence has validated the essential regulation of long non‐coding RNAs (lncRNAs) in the biological process of tumours. LncRNA PXN‐AS1 has been discovered to be as a tumour suppressor in pancreatic cancer; however, its function and mechanism remain greatly unknown in glioblastoma (GBM). Our present study indicated that PXN‐AS1 was highly expressed in GBM tissues and cells. Besides, the knock‐down of PXN‐AS1 was closely associated with the inhibitory proliferation and inducing apoptosis of GBM cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Glioblastoma cells show elevated levels of LncRNA PXN-AS1. Apoptosis of glioblastoma cells was promoted by PXN-AS1 inhibition through lowering Bcl-2 and elevating Bax ( Chen et al, 2020 ). There are low levels of TAF15 and LncRNA LINC00665 in glioma, on the contrary, high levels of MTF1, YY2, and GTSE1 are observed.…”
Section: Non-coding Rnas and Brain Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glioblastoma cells show elevated levels of LncRNA PXN-AS1. Apoptosis of glioblastoma cells was promoted by PXN-AS1 inhibition through lowering Bcl-2 and elevating Bax ( Chen et al, 2020 ). There are low levels of TAF15 and LncRNA LINC00665 in glioma, on the contrary, high levels of MTF1, YY2, and GTSE1 are observed.…”
Section: Non-coding Rnas and Brain Tumorsmentioning
confidence: 99%
“…Glioblastoma cells show elevated levels of LncRNA PXN-AS1. Apoptosis of glioblastoma cells was promoted by PXN-AS1 inhibition through lowering Bcl-2 and elevating Bax (Chen et al, 2020).…”
Section: Long Non-coding Rnas and Apoptosis In Brain Tumorsmentioning
confidence: 99%
“…Enhancer of zeste homologue 2 (EZH2) is a key member of the polycomb group genes and is able to promote the malignancy of cancer cells via inhibiting the expression of a variety of tumor suppressor genes (TSGs) [330]. EZH2 dually enhances the migration and proliferation of cancer cells, and targeting this oncogene factor is a promising strategy in cancer therapy [331,332]. In GC cells, STAT3 functions as an upstream mediator of EZH2.…”
Section: Stat3 As An Oncogene Factor In Gastric Cancermentioning
confidence: 99%
“…In melanoma cell lines, EZH2 is the only functional protein that binds to LINC-PINT in the nuclei, and LINC-PINT exerts an inhibitory effect on the pathogenesis of melanoma through enriching EZH2 to the promoter of its target genes [15]. Moreover, an evidence suggested that EZH2 mediates tumor progressions through regulating the expression levels of multiple genes, including KLF2, DKK-1, CDKN1C, ZEB1, ACE2, Robo4, P4HA1, and DUXAP8 [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%